Electroacupuncture Regulates Pain Transition Through Inhibiting PKCε and TRPV1 Expression in Dorsal Root Ganglion - Fang, Junfan; Wang, Sisi; Zhou, Jie; Shao, Xiaomei; Sun, Haiju; Liang, Yi; He, Xiaofen; Jiang, Yongliang; Liu, Boyi; Jin, Xiaoming; Fang, Jianqiao; Du, Junying (Frontiers in Neuroscience, 2021)
Many cases of acute pain can be resolved with few side effects. However, some cases of acute pain may persist beyond the time required for tissue injury recovery and transit to chronic pain, which is hard to treat. The mechanisms underlying pain transition are not entirely understood, and treatment strategies are lacking. In this study, the hyperalgesic priming model was established on rats to study pain transition by injection of carrageenan (Car) and prostaglandin E2 (PGE2). The expression levels of protein kinase C epsilon (PKCε) and transient receptor potential vanilloid 1 (TRPV1) in the L4–L6 dorsal root ganglion (DRG) were investigated. Electroacupuncture (EA) is a form of acupuncture in which a small electric current is passed between a pair of acupuncture needles. EA was administrated, and its effect on hyperalgesia and PKCε and TRPV1 expression was investigated. The PKCε–TRPV1 signaling pathway in DRG was implicated in the pain transition. EA increased the pain threshold of model animals and regulated the high expression of PKCε and TRPV1. Moreover, EA also regulated hyperalgesia and high TRPV1 expression induced by selective PKCε activation. We also found that EA partly increased chronic pain threshold, even though it was only administered between the Car and PGE2 injections. These findings suggested that EA could prevent the transition from acute to chronic pain by inhibiting the PKCε and TRPV1 expression in the peripheral nervous system.